The Impact of Timing of Concurrent Chemoradiation in Patients With High-Grade Glioma in the Era of the Stupp Protocol - Warren, Kwanza T.; Liu, Linxi; Liu, Yang; Milano, Michael T.; Walter, Kevin A. (Frontiers in Oncology, 2019)
Background: The purpose of this study is to provide a critical review of current evidence for the impact of time to initiation of chemoradiation on overall survival in patients with newly diagnosed high-grade gliomas treated with radiation and concurrent temozolomide chemotherapy. Methods: A literature search was conducted using PubMed/MEDLINE and EMBASE databases. Studies were included if they provided separate analysis for patients treated with current standard of care: radiation and concurrent temozolomide. Bias assessment was performed for each included study using the Newcastle-Ottawa Assessment Scale, with Karnofsky Performance Status (KPS) and extent of resection used for comparability. Results: The initial search yielded 575 citations. Based on the inclusion/exclusion criteria, a total of 10 retrospective cohort studies were included in this review for a total of 30,298 patients. Of these, one study described an indirect relationship between time to initiation of treatment and overall survival. One study found decreased survival only with patients with significantly longer time to treatment. Four studies found no significant effect of time to treatment on overall survival. The four remaining studies found that patients with moderate time to initiation had the best overall survival. Conclusion: This review provides evidence that moderate time to initiation of chemoradiotherapy in patients with high-grade gliomas does not lead to a significant decrease in overall survival, though the effect of significant delays in treatment initiation remains unclear.